2014
DOI: 10.1080/19942060.2014.11015520
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Turbulence Modulation by Cylindrical Particles in Round Jet

Abstract: In order to explore the turbulence modulation by cylindrical particles, the equation describing the probability density functions for the particle orientation, and the equations of Reynolds averaged Navier-Stokes, turbulence kinetic energy and turbulence dissipation rate with additional terms of particles are used and solved numerically in a round jet flow. The turbulence modulation at different axial distances from the nozzle exit in the initial region is given, and the effects of particle concentration, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…the average orientation gradually changes from horizontal state to vertical. However, from Table 1 it can be seen that, for a bulk settling of fibres of Re L~ O (10) and Re L~ O(100), no similar investigations seem to be available.…”
mentioning
confidence: 98%
“…the average orientation gradually changes from horizontal state to vertical. However, from Table 1 it can be seen that, for a bulk settling of fibres of Re L~ O (10) and Re L~ O(100), no similar investigations seem to be available.…”
mentioning
confidence: 98%
“…Swirling two-phase hydrodynamics using PDPA were performed by Sommerfield et al 1991,1993 [12,13] . In recent years, the direct numerical simulation (DNS) [18][19][20][21][22][23] , the large eddy simulation (LES) [24][25][26][27][28][29][30][31] , the Reynolds averaged Navier-Stokes simulation (RANS) [32][33][34][35][36][37][38][39][40][41] , have been applied to model and simulate the hydrodynamics of two-phase flows has been rapidly developed based on the computational fluid dynamics (CFD) technique. Gore et al1989 [42] characterized the turbulence modification into augmentation and attenuation categories using a developed intuitive parameter, which is the ratio of the particle diameter to a characteristic size of large eddies.…”
Section: Introductionmentioning
confidence: 99%
“…He found that turbulence intensity enhancement caused by cylindrical particles is smaller in the streamwise than that of near the nozzle exit, as well as directly proportional to particle concentration, Reynolds number and particle aspect ratio. Pakhomov et al 2015 [37] improved a two-phase turbulent Reynolds stresses model to predict the swirling particle dispersions in behind a sudden tube expansion. Fine particle attenuates the gas turbulence of up 25%.…”
Section: Introductionmentioning
confidence: 99%
“…In literature [4], the fluidization and agglomeration of the slender particles that was divided into a plurality of rigid segments by hinges were researched. Lin et al [5] put forward the control equations of particle sedimentation in static water based on the cylindrical particle oscillation frequency ω, which considered the influences of the oscillation, the torque and inter force of particles. Based on the lattice Boltzmann method, Lin et al [6][7][8] studied the influences of the aspect ratio, wall constraint and particles interaction on the settlement of slender particles, which reveals the orientation and motion characteristic of particles.…”
Section: Introductionmentioning
confidence: 99%